2020
DOI: 10.1186/s12870-020-02358-8
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated mechanisms of leaves and roots in response to drought stress underlying full-length transcriptome profiling in Vicia sativa L

Abstract: Background: Common vetch (Vicia sativa L.) is an important self-pollinating annual forage legume and is of interest for drought prone regions as a protein source to feed livestock and human consumption. However, the development and production of common vetch are negatively affected by drought stress. Plants have evolved common or distinct metabolic pathways between the aboveground and underground in response to drought stress. Little is known regarding the coordinated response of aboveground and underground ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 93 publications
1
26
0
Order By: Relevance
“…Salt cress could retain normal growth in 200 mM NaCl for a long time ( Inan et al, 2004 ). The plant leaves and roots follow distinct developmental trajectories to adapt to fluctuating environments that accompany the expression change of a number of stress-related genes ( Min et al, 2020 ). To obtain an overview of the salt response genes in Eutrema , the transcriptome of leaves and roots with or without 300 mM NaCl treatment for 24 h was investigated by the Illumina Hiseq2000 platform.…”
Section: Resultsmentioning
confidence: 99%
“…Salt cress could retain normal growth in 200 mM NaCl for a long time ( Inan et al, 2004 ). The plant leaves and roots follow distinct developmental trajectories to adapt to fluctuating environments that accompany the expression change of a number of stress-related genes ( Min et al, 2020 ). To obtain an overview of the salt response genes in Eutrema , the transcriptome of leaves and roots with or without 300 mM NaCl treatment for 24 h was investigated by the Illumina Hiseq2000 platform.…”
Section: Resultsmentioning
confidence: 99%
“…Combined transcriptomic and metabolomic analysis helps to reveal the complex mechanisms of plants in response to drought at the whole-plant level ( Arun et al, 2014 ). Previous researchers have studied the molecular mechanisms underlying plant drought resistance and have identified candidate genes such as NCED , HY5 , psbQ , GST and P5CS ; key metabolites such as phenylalanine, proline and flavonoids; a series of metabolites related to phenylpropanoid biosynthesis, starch and sucrose metabolism and proline; and important biosynthetic pathways and secondary metabolic pathways ( Savoi et al, 2016 ; Dalal et al, 2018 ; You et al, 2019 ; Zhao et al, 2019 ; Min et al, 2020 ). In this study, we identified several key candidate genes ( NCED , LHY , gpx , GST , WRKY33 , P5CS , PRODH , AOC3 , SOD1 , CAT , psbQ , psaK , glgC , etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The pathway enrichment of DEGs suggested that most of them were enriched in carbohydrate metabolism and signal transduction pathways. Carbohydrate metabolism were reported plays important roles in response to drought stress, the starch and sucrose metabolism is correlated with turgor pressure maintenance [ 44 , 45 ]. In addition, the signal transduction pathway was also found participated in the drought stress response [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%